Earnings management and investment efficiency - Linhares, Flavio Sergio; Costa, Fábio Moraes da; Beiruth, Aziz Xavier (Review of Business Management, 2018)
Purpose – To verify the relationship between the quality of the accounting information, measured by earnings management, and the efficiency of investments made by Brazilian companies listed on the BM&FBovespa. Design/methodology/approach – Firstly, the investment efficiency benchmark was established, analyzing the level of investment and the growth in sales as shown in equation (1). After this classification, the results of the extreme quartiles, which were classified as over/ under investment, were used as dependent variables to analyze the relationship between income and investment management above or below predictable levels. Finally, to test this relationship, a multinomial logistic regression was used to evaluate the probability of over and under investments in companies that practice earnings management, compared to the benchmark. The sample that served as the basis for this study is composed of all the publicly-held companies that had or still have shares listed on the BM&FBOVESPA, covering the period from 1996 to 2012. Findings – The data analysis revealed empirical evidence that earnings management is positively related to levels investment and this can interfere in the probability of a company being classified as under or over investing. Therefore, based on the results found, it is confirmed that “the higher the level of earnings management, the greater the probability of the company deviating from the ideal level of investment.” Originality/value – The results were consistent with the idea that the quality of accounting information plays a relevant role for managers in order to analyze the efficiency of investments.